Objetos sonoros caninos (2023)
The concept of the sound object comes from the meticulous study of Pierre Schaeffer regarding the nature of sound and music from a technical and phenomenological perspective, leading to the creation of a broad typomorphology of sound. In this work, these tools are revisited in order to compose four pieces using as the sole material sounds from dogs (canis familiaris), which were previously identified and subsequently induced. Thanks to this process of review and exploration, a better understanding of the musical phenomenon was achieved, as a highly dependent perception of sound based on regular and oblique rhythmic categories introduced by Pierre Schaeffer. It was proposed to adopt a more gestalt perspective on the sound object, classically conceived as a unit perceived in its own material and perceptual dimensions, in the practice of composition. This is due to the fact that its appearance can change when compared with other objects, and the ear can become desensitized through prolonged repetition. Hence, the practice of comparative listening is proposed.